A robotic system for concrete repair preparation. - Chamberlain, D.A.
The widespread deterioration of reinforced concrete structures and the associated need for inspection and repair are reviewed. Towards this end, robotic handling of a NDT probe and blasting tool is investigated. A single-pass method for the detection of rebars is presented that takes into account the effects of transverse, parallel, and lapped bars relative to the detection of an isolated rebar. Examples of rebar detection trials are given, all of which are encouraging. While isolated bars are perfectly detected, parallel bars are reliably found where their pitch exceeds 100 turn. The effect of transverse bars is readily catered for by using an offset equivalent to an ambient signal value. In respect to lapped bars where different arrangements are possible, the main progress is in achieving images that help to distinguish these. While existing automatic and robotic systems "excavate to strength," a selective approach for the removal of defective concrete, there is the need to produce good geometry in order to make repairs last. This "excavation to geometry" approach requires the system to alter its cutting-power parameters or dwell time (extended application on higher strength areas). The presented robotic system aims to establish sensor and control technology that will make possible such real-time control of the erosion process. In this, advantage is to be taken of inspection and NDT-based prediction of the condition and in situ strength of the concrete component
Keywords: Ambient signal value; Blasting tool; Concrete deterioration; Concrete repair; Control technology; Cutting-power parameters; Dwell time; Erosion process; Excavation to geometry approach; Hydro-erosion.; Inspection; Isolated bars; Lapped bars; Offset; Parallel bars; Real-time control; Rebar detection; Reinforced concrete structures; Robotic handling; Sensor technology; Single-pass method; Transverse bars